The education skills trap in a dependent market economy. Romania's case in the 2000s. Issue 1 (March 2018) - Tarlea, Silvana; Freyberg-Inan, Annette
Abstract: We discuss the political economic development of Romania since 1989, with a focus on the evolution of higher education (HE). First, we place this evolution in the context of demand for HE by prospective students and employers, focusing on the low demand for skills in the MNC-dominated Romanian economy. Second, we provide empirical insight on indicators of quality, enrolment, and funding as key features of the HE system. We argue that Romania has evolved into a dependent market economy entrenched in a low-skills equilibrium, and that the weakness of the HE system is a key element in this process.